Review of the Feasibility of Jember Regency Library Space Against Regulatory Standards - Ananta Yanuar Setiawan; Ibrahim Tohar; Andarita Rolalisasi (Kirana Publisher (KNPub), 2026)
Reviewing the suitability of library space is a crucial step in assessing the capacity of public service institutions to fulfill educational, comfort and accessibility functions according to the National Library Standards (SNP). This research aims to evaluate the physical and functional conditions of the Jember Regency Library Room based on national regulations such as Law no. 43 of 2007 and SNP 003:2011. The method used is descriptive qualitative through field observation and literature study. The focus of the evaluation includes aspects of space zoning, availability of supporting facilities, accessibility for people with disabilities, and security systems. The results of the study show that although the Jember Library has carried out its basic functions, there is a need for improvement in the aspects of inclusive accessibility and efficiency of multimedia layout to answer the dynamic needs of modern society. Fulfilling regulatory standards is the foundation for creating a functional and competitive library.